2005
DOI: 10.1002/rcm.2195
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and characterization of minor reactive metabolites using stable‐isotope trapping in combination with tandem mass spectrometry

Abstract: Stable-isotope trapping combined with mass spectrometry (MS) neutral loss scanning has recently been developed as a high-throughput method for the in vitro screening of major reactive metabolites. In fact, detection and identification of minor reactive metabolites are equally important since the minor metabolites, even though at low levels, may be highly reactive and also play an important role in drug-induced adverse reactions. In this study, 2-acetylthiophene, clozapine, troglitazone and 7-methylindole were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 15 publications
(19 reference statements)
2
45
0
Order By: Relevance
“…Among patients treated with troglitazone, the prevalence of an abnormal increase in the levels of amino transferases was much higher in the subjects with double null alleles of GSTM1 and GSTT1 than in the subjects with wild-type alleles. In the proposed metabolic pathways of troglitazone, previous reports showed that reactive metabolites are produced by P450 enzymes such as CYP3A4 and were conjugated with GSH to form five kinds of GSH conjugates (Kassahun et al, 2001;Yan et al, 2005). These reports suggest that GSTM1 and GSTT1 are involved in the detoxification of reactive metabolites of troglitazone.…”
Section: Introductionmentioning
confidence: 84%
“…Among patients treated with troglitazone, the prevalence of an abnormal increase in the levels of amino transferases was much higher in the subjects with double null alleles of GSTM1 and GSTT1 than in the subjects with wild-type alleles. In the proposed metabolic pathways of troglitazone, previous reports showed that reactive metabolites are produced by P450 enzymes such as CYP3A4 and were conjugated with GSH to form five kinds of GSH conjugates (Kassahun et al, 2001;Yan et al, 2005). These reports suggest that GSTM1 and GSTT1 are involved in the detoxification of reactive metabolites of troglitazone.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, the formation of menthofuran corresponds to loss of two protons, and its further conversion into isomeric aldehyde creates an electrophile to be trapped. 20 The similar reaction with additional double-bond opening thus corresponds to the detected conjugates having molecular formulas equal to direct pulegone conjugation, and the number of hydroxylations and hydrogenations to the menthofuran structure also provide the basis for other detected pulegonerelated GSH conjugates. Also supporting this, seven GSH conjugates were found for menthofuran, even though the efficiency of GSH to trap these furan-related hard electrophiles is reported to be low, 31 and no GSH-trapped menthofuran conjugates have been reported previously.…”
Section: Pulegone and Menthofuranmentioning
confidence: 95%
“…The poor specificity of positive ion mode NL scanning was improved by using a 1:1 mixture of stable isotope labeled glutathione ( 13 C 2 , 15 N-glutathione) and nonlabeled glutathione as a trapping agent, leading to an easily distinguishable molecular ion doublet with three mass units (3 Da) separation for the real GSH conjugates. [19][20][21] Along with the development of new mass spectrometers, Zheng et al 22 used LC/MS/MS with a hybrid triple quadrupole linear ion trap (Q-Trap) mass spectrometer for highly sensitive multiple reaction monitoring (MRM) and data-dependent ion trap MS/MS product ion scanning to screen GSH conjugates. This approach however needed a laborious prediction of the possible reactive metabolites, and consecutive generation of the MRM reactions for the predicted metabolites, limiting the use of the approach for high-throughput screening and leaving the unexpected conjugates undetected.…”
mentioning
confidence: 99%
“…Recent examples of this application include the use of labeled glutathione as a trapping agent. 109 show improved reproducibility over their predecessors, issues such as matrix effects, due to co-elution of compounds not detected by the mass spectrometer, can introduce unwanted analytical variability. Internal standard is customarily added prior to sample preparation to compensate for losses during this and the chromatographic-mass spectrometric processes and to account for matrix effects.…”
Section: -108mentioning
confidence: 97%